Entrepreneurship in emerging market economies: Contemporary issues and perspectives. (March 2014) - Smallbone, David; Welter, Friederike; Ateljevic, Jovo
Entrepreneurship increasingly is becoming a global phenomenon, although its nature, extent and contribution to economic development varies according to the context in which it occurs. However, most of the conceptual development in the field of entrepreneurship has occurred in, or assumed, mature market conditions. This short introduction critically evaluates why we need to study other contexts such as emerging markets, and outlines the topics of the articles in the special issue.